Fatigue cracking behavior of 6063 aluminum alloy for fitting clamps of overhead conductor lines. (25th December 2015) - Zeng, L.R.; Song, Z.M.; Wu, X.M.; Li, C.H.; Zhang, G.P.
Abstract: The 6063 aluminum alloy is a candidate for fitting clamps to fasten and connect the Al alloy overhead conductor lines. The Al alloy fitting clamps with different extents of stress concentration may become quite dangerous under cyclic loading due to the wind-induced swing of the conductor lines. In this study, fatigue properties and cracking behavior of the 6063 aluminum alloy were investigated using three-point-bending specimens with different notch angles. The relationship between the nominal fatigue cracking resistance and the notch angle of the Al alloy specimens was obtained. Fatigue damage and notch angle-dependent cracking behaviors were evaluated. Fatigue reliability of the 6063 alloy specimens with different stress concentration factors was discussed combined with a grain size of the alloy. Graphical abstract: Highlights: Fatigue cracking resistance from the notch in the 6063 alloy increases with increasing the notch angle. Stress concentration factor dominates the extent of fatigue cracking damage of the 6063 alloy. Initial fatigue crack growth rate of the 6063 alloy at the notch root depends on notch angle.